Transgenic Killer Commensal Bacteria as Mucosal Protectants - Luciano Polonelli (The Scientific World Journal)
As first line of defense against the majority of infections and primary site for their transmission, mucosal surfaces of the oral cavity and genitourinary, gastrointestinal, and respiratory tracts represent the most suitable sites to deliver protective agents for the prevention of infectious diseases. Mucosal protection is important not only for life threatening diseases but also for opportunistic infections which currently represent a serious burden in terms of morbidity, mortality, and cost of cures. Candida albicans is among the most prevalent causes of mucosal infections not only in immuno- compromised patients, such as HIV-infected subjects who are frequently affected by oral and esophageal candidiasis, but also in otherwise healthy individuals, as in the case of acute vaginitis. Unfortunately, current strategies for mucosal protection against candidiasis are severely limited by the lack of effective vaccines and the relative paucity and toxicity of commercially available antifungal drugs. An additional option has been reported in a recent